Comparative Analysis of the Simple WISP and Some Prominent MCDM Methods: A Python Approach - Stanujkić, Dragiša; Karabašević, Darjan; Popović, Gabrijela; Zavadskas, Edmundas Kazimieras; Saračević, Muzafer; Predrag S. Stanimirović; Vasilios N. Katsikis; Ulutaş, Alptekin; Meidute-Kavaliauskiene, Ieva (Axioms, 2021)
This article presents a comparison of the results obtained using the newly proposed Simple Weighted Sum Product method and some prominent multiple criteria decision-making methods. For comparison, several analyses were performed using the Python programming language and its NumPy library. The comparison was also made on a real decision-making problem taken from the literature. The obtained results confirm the high correlation of the results obtained using the Simple Weighted Sum Product method and selected multiple criteria decision-making methods such as TOPSIS, SAW, ARAS, WASPAS, and CoCoSo, which confirms the usability of the Simple Weighted Sum Product method for solving multiple criteria decision-making problems.